Comparative study of bacterial strains and antibiotic susceptibility tests between chronic tonsillitis patients with IgA nephropathy and without nephritis. (November 2013) - Huang, Hongdong; Sun, Weiming; Liang, Yumei; Peng, Youming; Long, Xi-Dai; Liu, Zhihua; Tian, Ru; Bai, Chengli; Cai, Genshen
Abstract Aim: The purpose of the present study was to detect bacterial strains and antibiotic susceptibility in chronic tonsillitis patients with IgA nephropathy (IgAN) and without nephritis, in order to provide evidence for clinical therapy and pathogenesis of IgAN. Methods: A total of 53 patients with IgAN (group A) and 53 chronic tonsillitis patients without nephritis (group B) underwent tonsillectomy. The tonsil tissues of patients were collected under sterile condition. The bacteria in the tonsil crypt of patients in both groups were isolated and identified for antibiotic susceptibility test by the manual routine of the laboratory and also with the autoScan/Microscan system. Results: There were bacteria in each specimen in both groups. The bacteria detection rate was 100%, but there was no significant difference between two groups (p > 0.05). The 522 strains of bacteria in group A and 494 strains of bacteria in group B were isolated. Streptococcus. Neisseria, Hemophilus parainfluenzae. Staphylococcus. Bacillus proteus and Streptococcus pneumoniae were detected in both groups, but there was no significant difference in the types of bacteria between the two groups (all p > 0.05). Alpha streptococcus was the most common in both groups. The antibiotic susceptibility test showed that there was no significant difference in the susceptibility to penicillin, chloramphenicol, macrolides, cephalosporin, gentamicin, amikacin sulphate, norfloxacin, ciprofloxacin, rifampicin and vancomycin between two groups (all p > 0.05). Conclusions: Alpha streptococcus in both two groups can be detected and is the most common. There was no significant difference in bacterial strains and antibiotic susceptibility between two groups.